Synthetic incorporation of Nile Blue into DNA using 2′-deoxyriboside substitutes: Representative comparison of (R)- and (S)-aminopropanediol as an acyclic linker - Lachmann, Daniel; Berndl, Sina; Wolfbeis, Otto S.; Wagenknecht, Hans-Achim (Beilstein Journal of Organic Chemistry, 2010)
The Nile Blue chromophore was incorporated into oligonucleotides using “click” chemistry for the postsynthetic modification of oligonucleotides. These were synthesized using DNA building block 3 bearing an alkyne group and reacted with the azide 4. (R)-3-amino-1,2-propanediol was applied as the linker between the phosphodiester bridges. Two sets of DNA duplexes were prepared. One set carried the chromophore in an A-T environment, the second set in a G-C environment. Both were characterized by optical spectroscopy. Sequence-dependent fluorescence quenching was applied as a sensitive tool to compare the stacking interactions with respect to the chirality of the acyclic linker attachment. The results were compared to recent results from duplexes that carried the Nile Blue label in a sequentially and structurally identical context, except for the opposite chirality of the linker ((S)-3-amino-1,2-propandiol). Only minor, negligible differences were observed. Melting temperatures, UV–vis absorption spectra together with fluorescence quenching data indicate that Nile Blue stacks perfectly between the adjacent base pairs regardless of whether it has been attached via an S- or R-configured linker. This result was supported by geometrically optimized DNA models.
Keywords: cycloaddition; fluorescence; glycol; oligonucleotide; phenoxazinium; phosphoramidite